Effects of alternative dietary lipid sources on growth performance, health status and fillet fatty acid composition of hybrid sturgeon (Acipenser baeri Brandt ♀ × Acipenser schrenckii Brandt ♂). (28th August 2020) - Yu, Huanhuan; Xing, Wei; Li, Tieliang; Xu, Guanling; Ma, Zhihong; Jiang, Na; Luo, Lin
Abstract: An 8‐week trial was conducted to determine the effects of total replacement of 12.9% fish oil (FO) with soybean oil (SBO), peanut oil (PNO), sunflower seed oil (SFSO), corn oil (CO) and canola oil (CNO) on growth performance, health status and fillet fatty acid composition of hybrid sturgeon (194.28 ± 0.14 g). Compared to the FO group, dietary SBO decreased growth performance ( p  < .05), increased serum glucose and hepatic lipid content ( p  < .05). No obvious adverse effects on growth performance and health status were observed in PNO, SFSO and CO groups ( p  > 0.05). The fish fed with CNO had increased growth performance ( p  < .05), reduced serum ALT, AST, LDL‐C ( p  < .05) and enhanced serum GSH‐Px, T‐AOC, and LZM, MPO, C4 ( p  < .05). The contents of C18:1n9, C18:2n6, and ∑n‐3 PUFA and ∑n‐6 PUFA in fillets showed a positive linear correlation with the diets ( p  < .05). In summary, PNO, SFSO and CO are probable alternative lipid sources to fully replace FO. Hybrid sturgeon prefers to use CNO as a lipid source with improved growth performance and health status. The fillet fatty acid composition mirrors the dietary fatty acid composition.